Latin American perspectives on person-centered medicine (2016)
Person-centered medicine (PCM) is a programmatic global initiative led by the International College of Person-Centered Medicine. It has recently emerged in Latin America. It requires the use of scientific research as an instrument to generate the best clinical evidence, and humanism as the essence of medicine to help mankind. It is focused on not only combatting disease but also promoting the display of healthy human being potentials towards achieving well-being and comprehensive growth. Although the humanism of medicine in Latin America has been a distinctive characteristic of its practice, now, there is a worrying decline in its impact on healthcare. This article summarizes the Latin American perspective from four countries. Needs and experiences are compared and responses that arise in view of the dehumanizing influence of technology and health management as a consumption good are described. © 2016, Instituto Nacional de Salud. All rights Reserved.